PELATIHAN BUDAYA LOKAL DAN WISATAWAN PADA PRAMUWISATA DI OBJEK WISATA SANGEH, KABUPATEN BADUNG - SUDANA SUDANA; M. SUKANA; I N. ARIANA; I M. ADIKAMPANA; I G.B. SASRAWAN MANANDA; I M. SENDRA (Lembaga Penelitian dan Pengabdian kepada Masyarakat, 2008)
ABSTRACT The holy monkey forest Sangeh is well-known of Macaca Fascicularisin in the 10 ha of pala (Dipterocarpus Trinervis) forest. Beside the forest which is hundred years old, these attraction also have Bukit Sari temple since 17th century when the Mengwi kingdom exist. Others attraction are Melanting, Tirta, Anyar temple, and lanang wadon (male-female) tree. These tourist attraction is managed by local traditional village (desa adat) Sangeh. The guide has a big role in tourism development. In order to do their duty, they have to make the tourist understand and pay attention to them, so it can give good image for the tourist attraction. The cross cultural understanding is the key success to improve the interaction quality between host and guest in the service context. The guide needs to pay attention of the different culture in communication as they interact with the tourist intensively. The local guides understand well the background of Sangeh tourist attraction, history, tradition, local genius, international politic, geography, and gastronomy. However, the skill of the local guide in speaking English language are varieted, some people can speak fluently but some of them not. Most of the local guide was not joining the foreign language course; however, some of them had worked in the big hotel. They also have some difficulties to communicate foreign languages and that make little conversation with the tourist that visit Sangeh. From the tourist culture aspect shows that the local guides have lack understanding of history, site background, and customs of the tourist. The local guides also have some difficulties after escorting the tourist guides as they don’t want the tourist think that they expect the tipping aggresively.